Bi2O3/nylon multilayered nanocomposite membrane for the photocatalytic inactivation of waterborne pathogens and degradation of mixed organic pollutants. Issue 1 (6th January 2021) - Gadhi, Tanveer A.; Qureshi, Aizaz; Channa, Najeebullah; Mahar, Rasool Bux; Chiadò, Alessandro; Novara, Chiara; Tagliaferro, Alberto
Abstract : Bi2 O3 /nylon multilayered nanocomposite membrane was fabricated by electrospinning and effectively used to degrade organic dye pollutants and pathogens through ROS produced by photocatalysis. Abstract : A powder semiconductor α/β-Bi2 O3 was synthesized via solid state thermal annealing and further composited with a multilayered nylon fibrous membrane via electrospraying. The successful integration of nano-sized α/β-Bi2 O3 into the nylon membrane was confirmed by XRD, FESEM images, UV-vis, FT-IR and Raman analyses. The nanocomposite membrane displayed a visible light-responsive catalytic ability with an energy bandgap of 2.78 eV estimated from the data of DRS. The activity of the composite membrane was examined in a continuous mode reactor for the degradation of separate and mixed solutions of anionic (indigo carmine) and cationic (rhodamine B) organic pollutants. Moreover, the composite membrane exhibited antibacterial properties towards E. coli, a waterborne pathogen, as revealed by the obtained growth inhibition during the Kirby–Bauer and liquid culture tests. The inactivation of E. coli was confirmed by live/dead cell staining using fluorescence imaging. Finally, a mixed solution of organic dyes at different concentration, as well as the recycle of the membrane, showed the stability and potential of the α/β-Bi2 O3 composite membrane for the removal of organic pollutants and inactivation of the waterborne pathogen.